2022
DOI: 10.3390/foods11213523
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Isoflavones in Pueraria by UHPLC-Q-Orbitrap HRMS and Study on α-Glucosidase Inhibitory Activity

Abstract: Pueraria is a rich source of bioactive compounds, but there is a lack of comprehensive information concerning its composition. Therefore, a UHPLC-Q-Orbitrap HRMS method was developed to identify and quantify bioactive compounds in pueraria. Twelve isoflavones were quantified, with puerarin being the most abundant, followed by puerarin 6″-O-xyloside, 3′-methoxy puerarin, and 3′-hydroxy puerarin. A further 88 bioactive components in eight categories were also tentatively identified. The 12 isoflavones, except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, there are still a number of flavonoid compounds remaining unidentified and isolated. Several studies have suggested that the antidiabetic effect of kudzu extracts is primarily attributed to puerarin by inhibiting PTP1B and AG. , However, these studies mainly focused on the total extract or puerarin, and the potential contributions and modes of action of other active compounds remain unknown. Here, we isolated and characterized flavonoid compounds from kudzu and examined their biological activities against three targets, including SGLT2, AG, and PTP1B.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still a number of flavonoid compounds remaining unidentified and isolated. Several studies have suggested that the antidiabetic effect of kudzu extracts is primarily attributed to puerarin by inhibiting PTP1B and AG. , However, these studies mainly focused on the total extract or puerarin, and the potential contributions and modes of action of other active compounds remain unknown. Here, we isolated and characterized flavonoid compounds from kudzu and examined their biological activities against three targets, including SGLT2, AG, and PTP1B.…”
Section: Introductionmentioning
confidence: 99%